If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -8 = 15x + -21 Reorder the terms: -8 + 8x = 15x + -21 Reorder the terms: -8 + 8x = -21 + 15x Solving -8 + 8x = -21 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. -8 + 8x + -15x = -21 + 15x + -15x Combine like terms: 8x + -15x = -7x -8 + -7x = -21 + 15x + -15x Combine like terms: 15x + -15x = 0 -8 + -7x = -21 + 0 -8 + -7x = -21 Add '8' to each side of the equation. -8 + 8 + -7x = -21 + 8 Combine like terms: -8 + 8 = 0 0 + -7x = -21 + 8 -7x = -21 + 8 Combine like terms: -21 + 8 = -13 -7x = -13 Divide each side by '-7'. x = 1.857142857 Simplifying x = 1.857142857
| 2d+18=2-6(d+7) | | =8.041840047611249e+17 | | 5=1-a | | 0.2s=16 | | =0.2e+17 | | 92=c+3 | | 4x^2+5x-440=0 | | 220=-12.5x | | P+-3=5 | | -35+9= | | 32x+12y+52= | | 0.15-1.8=0.3(x-5) | | 8-7x-4=-57+5x-11 | | 8z+5=8 | | C+-6=-10 | | ln(6x+14)=2 | | 25x^2-30x=72 | | -x-15=x-5 | | f(x)=3+0.1x | | 3x-6(x-12)=57 | | 3n+3(n+4)=42 | | 27x+-171=76+8x | | 159=-3x-3(-6x-18) | | (7x+27)+4x=(x+9)+(2x+154) | | 0=-5x+5(2x+6) | | -6x-15=7x+24 | | -2v-2=-14-5v | | 68=5x+2(2x+7) | | X/3=x/5-18 | | -49=-5x+4(-2x+4) | | 6x+26-44x-20=8x | | 3-12x=147 |